2021
DOI: 10.4103/jfmpc.jfmpc_2412_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of levels of oxidative stress as a potential biomarker in patients with rheumatoid arthritis

Abstract: Objectives: One of the most prevalent autoimmune disease globally, rheumatoid arthritis (RA) is caused by interplay of multiple inflammatory mediators in specific joints. Altered redox balance is one of the key factors in pathophysiology of RA. This study aims to find whether oxidative stress in peripheral blood neutrophil correlates with the disease activity and disability associated with it. Methods: Ten healthy controls and 29 RA patients with moderate to severe dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In previous studies, increased ROS levels have been reported in patients with RA (24,25); therefore, the present study investigated the relationship between SNP rs16917496 and ROS levels in patients with RA. ROS levels were higher in the CC genotype carriers (1011.500±536.426 vs. 548.616±190.508, P=0.032, Fig.…”
Section: Genementioning
confidence: 95%
“…In previous studies, increased ROS levels have been reported in patients with RA (24,25); therefore, the present study investigated the relationship between SNP rs16917496 and ROS levels in patients with RA. ROS levels were higher in the CC genotype carriers (1011.500±536.426 vs. 548.616±190.508, P=0.032, Fig.…”
Section: Genementioning
confidence: 95%
“…With this device, it is possible to determine the redox balance in the sample using the d-ROMs Fast (measurement of free radicals) and PAT (measurement of antioxidant power) tests and, therefore, to calculate the OSI. In most cases, the study of OS in various diseases is conducted on blood samples taken from a peripheral vein; however, in this way, only the “general” oxidative state of the patient is analyzed [ 53 , 54 , 55 , 56 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, excessive ROS is toxic to non-FSLs and triggers ferroptosis in these cells; however, ROS accumulation has a pro-proliferative and pro-survival role in FSLs. Several studies have attempted to explore alternative methods to assess the disease activity and prognosis of RA by monitoring the levels of ROS, mtDNA, and other markers of oxidative stress ( 46 , 54 , 55 ). However, further studies and explorations are still needed to address the use of oxidative stress markers in the treatment of RA.…”
Section: Association Between Ferroptosis and Ramentioning
confidence: 99%
“…alternative methods to assess the disease activity and prognosis of RA by monitoring the levels of ROS, mtDNA, and other markers of oxidative stress (46,54,55). However, further studies and explorations are still needed to address the use of oxidative stress markers in the treatment of RA.…”
Section: Lipid Peroxidation and Oxidative Stress In Ramentioning
confidence: 99%